2013
DOI: 10.1177/0269215513501524
|View full text |Cite
|
Sign up to set email alerts
|

Does progressive resistance strength training as additional training have any measured effect on functional outcomes in older hospitalized patients? A single-blinded randomized controlled trial

Abstract: The results indicate that for older hospitalized patients progressive resistance strength training as additional training may have an effect compared to standard care, but no statistically significant effects were demonstrated when measured by functional outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 38 publications
10
18
0
Order By: Relevance
“…There were considerable differences in 'usual care' across studies, possibly due to differences in clinical practice and healthcare provision. Six studies described the exercise provision in the usual care groups [20][21][22][23][24][25]. Exercise was prescribed as two 45 minute sessions weekly [24] three times a…”
Section: Usual Carementioning
confidence: 99%
See 4 more Smart Citations
“…There were considerable differences in 'usual care' across studies, possibly due to differences in clinical practice and healthcare provision. Six studies described the exercise provision in the usual care groups [20][21][22][23][24][25]. Exercise was prescribed as two 45 minute sessions weekly [24] three times a…”
Section: Usual Carementioning
confidence: 99%
“…All studies described the location of the intervention. Five trials were conducted solely in hospital [20][21][22][23]27], three trials had both in-hospital and post discharge components [24,26,28], and one trial occurred in the patients' home [25]. Of the six in-hospital studies, four reported starting the rehabilitative intervention within 72 hours of admission [20,23,26,27].…”
Section: Description Of the Interventionsmentioning
confidence: 99%
See 3 more Smart Citations